Sociodemographic factors and current contraceptive use among ever-married women of reproductive age: Analysis of the 2017 Indonesia Demographic and Health Survey data - Ni Kadek Ayu Dwi Utami Ds; Dewa Nyoman Wirawan; Luh Seri Ani (Universitas Udayana, 2019)
Background and purpose: Globally, the number of new contraceptive users in mid-2017 was only around half of the target. According to the results of the Indonesian Demographic and Health Survey (IDHS), the use of all methods of contraception in Indonesia has increased but is still lower than the target. This study aims to determine the factors associated with the use of contraception in Indonesia. Methods: This study uses secondary data from the 2017 IDHS that was carried out in 34 provinces in Indonesia. The total sample was 35,681 of 49,627 women aged 15-49 years. The dependent variable was current contraceptive use. The independent variables consisted of socio-demographic and socio-economic factors, knowledge, discussion with husband, and access to health services. Data analysis was performed through a binary logistic regression test to obtain the adjusted odd ratio of each factor. Results: The proportion of current contraceptive use was found to be 63.6% (95%CI: 63.2-64.0%). Factors related to current contraceptive use were family planning information from health workers (AOR=1.67; 95%CI: 1.59-1.77), maternal age of 35-44 years (AOR=1.54; 95%CI: 1.42-1.66), maternal age of 25-34 years (AOR=1.37; 95%CI: 1.27-1.48), maternal age ≥45 years (AOR=0.75; 95%CI: 0.68-0.82), living in the Java-Bali region (AOR=1.28; 95%CI: 1.22-1.35), living in rural areas (AOR=1.07; 95%CI: 1.01-1.12), having more than two living children (AOR=1.52; 95%CI: 1.44-1.60), level of education not attending school until not graduating from high school (AOR=1,46; 95%CI: 1.35-1.59), high school graduation level (AOR=1.25; 95%CI: 1.16-1.35), not working status (AOR=1.08; 95%CI: 1.03-1.13), medium wealth index (AOR=1.07; 95%CI: 1.00-1.14) and good knowledge (AOR=1.17; 95%CI: 1.11-1.23). Conclusion: The proportion of current contraceptive use in couples of childbearing age in Indonesia has not reached the government target. Factors that were more likely to increase current contraceptive use were family planning information from health workers, age, region, number of living children, mothers’ education, and knowledge. The family planning program in Indonesia should therefore consider those factors to increase the current contraceptive use.